Outcomes after endovascular treatment for anterior circulation stroke presenting as wake-up strokes are not different than those with witnessed onset beyond 8 hours. (17th October 2014) - Aghaebrahim, Amin; Leiva-Salinas, Carlos; Jadhav, Ashutosh P; Jankowitz, Brian; Zaidi, Syed; Jumaa, Mouhammad; Urra, Xabi; Amorim, Edilberto; Zhu, Guangming; Giurgiutiu, Dan-Victor; Horev, Anat; Reddy, Vivek; et al.
Abstract : Objective: Previous studies have suggested that patients with wake-up stroke (WUS) may have superior outcomes compared with patients with a witnessed late time of onset after revascularization. We sought to test this hypothesis in patients with anterior circulation large vessel occlusion stroke (ACLVOS) treated with endovascular therapy beyond 8 h from time last seen well (TLSW). Methods: A single center retrospective review of a prospectively acquired database of consecutive patients was performed to identify patients presenting beyond 8 h of TLSW with radiographic evidence of ACLVOS, small core, and large penumbra who subsequently underwent endovascular treatment. Results: We identified 206 patients. Patients were divided into two groups: (1) patients with WUS (38%, n=78) and (2) patients with witnessed onset beyond 8 h (62%, n=128). The groups were similar in age, baseline National Institutes of Health Stroke Scale score, TLSW to reperfusion, baseline infarct volume, and rate of successful recanalization. Rates of good outcome (modified Rankin Scale score of 0–2 at 90 days, 43% vs 50%, p=0.3), parenchymal hematoma (9% vs 5.5%, p=0.3), and final infarct volume (75.2 vs 61.4 mL, p=0.6) were comparable. Multivariate analysis identified age (OR=0.95, 95% CI 0.91 to 0.99, p<0.042), successful recanalization (OR 6.0, 95% CI 1.5 to 23.5, p=0.009), and final infarct volume (OR 0.98, 95% CI 0.97 to 0.99, p<0.001) but not mode of presentation as predictors of favorable outcomes. Conclusions: Rates of good outcomes, parenchymal hematoma, and final infarct volumes following endovascular treatment may not be different in patients with WUS compared with patients with witnessed onset of symptoms beyond 8 h.